The use of SDRAM for synchronized switching of television signals - Панченко, Борис Евгеньевич; Печенюк, Дмитрий Андреевич (Technology audit and production reserves, 2015)
The investigation of the possibility of using SDRAM-chip for synchronization of pre-unsynchronized television signals. Such type of memory can significantly reduce the cost of the synchronized switching television signals in the case of multi-user mode and a large number of sources (1000 and more) and build a switching system over a large area. Timing diagrams of the digital switching unit, which allows drawing conclusions about the possibility of using such devices for solving the problem of synchronization. This is important to optimize the cost of construction and redesign of the system when the location of the sources on a large territory may be situational and for a brief time to change. This approach also makes it possible to minimize the size of the switching system and fiber-optic camera channels, which do not depend on the number of service sources. According to the authors, such technical solution is proposed for the first time.